A computational framework for guiding the MOCVD-growth of wafer-scale 2D materials - Kasra Momeni; Yanzhou Ji; Nadire Nayir; Nurruzaman Sakib; Haoyue Zhu; Shiddartha Paul; Tanushree H. Choudhury; Sara Neshani; Adri C. T. van Duin; Joan M. Redwing; Long-Qing Chen (npj Computational Materials, 2022)
Abstract Reproducible wafer-scale growth of two-dimensional (2D) materials using the Chemical Vapor Deposition (CVD) process with precise control over their properties is challenging due to a lack of understanding of the growth mechanisms spanning over several length scales and sensitivity of the synthesis to subtle changes in growth conditions. A multiscale computational framework coupling Computational Fluid Dynamics (CFD), Phase-Field (PF), and reactive Molecular Dynamics (MD) was developed – called the CPM model – and experimentally verified. Correlation between theoretical predictions and thorough experimental measurements for a Metal-Organic CVD (MOCVD)-grown WSe2 model material revealed the full power of this computational approach. Large-area uniform 2D materials are synthesized via MOCVD, guided by computational analyses. The developed computational framework provides the foundation for guiding the synthesis of wafer-scale 2D materials with precise control over the coverage, morphology, and properties, a critical capability for fabricating electronic, optoelectronic, and quantum computing devices.